Prevalence of Allergic Sensitization to Conifer Pollen in a High Cypress Exposure Area. Issue 4 (October 2016) - Domínguez-Ortega, Javier; López-Matas, María Ángeles; Alonso, María Dolores; Feliu, Angélica; Ruiz-Hornillos, Javier; González, Emma; Moya, Raquel; Carnés, Jerónimo
Background: Sensitization to Finales (Cupressaceae and Pinaceae) has increased dramatically in recent years. The prevalence of sensitization in different geographic areas is related to exposure to specific pollens. Objectives: To investigate the prevalence of allergy to different conifer pollens, describe the characteristics of patients with such allergy, and identify the involved allergens. Methods: Patients were recruited at five hospitals near Madrid. Extracts from conifer pollen were prepared and used in skin-prick testing. Wheal sizes were recorded, and serum samples obtained from patients with positive reactions to Cupressus arizonica and/or Pinus pinea. The specific immunoglobulin E value to C. arizonica and Cup a 1 was determined. Individual immunoblots for each patient and with a pool of sera were performed. Allergenic proteins were sequenced by using liquid chromatography-tandem mass spectrometry. Results: Of 499 individuals included in the study, 17 (14%) had positive skin-prick test results to some conifer pollen extracts. Sixty-four patients had positive results to C. arizonica (prevalence 12.8%) and 11 had positive results to P. pinea (2.2%). All the patients had respiratory symptoms (61.4% during the C. arizonica pollination period), and 62.9% had asthma. Approximately 86% of the patients had positive specific immunoglobulin E results to C. arizonica and 923% had positive results to Cup a 1. Fourteen different bands were recognized by immunoblot; the most frequent bands were those detected at 43, 18, 16, and 14 kDa. All sequenced proteins corresponded to Cup a 1. Conclusion: Allergy to conifer pollen could be considered a relevant cause of respiratory allergy in central Spain. Asthma was more frequent than in other studies. We only identified Cup a 1 as involved in sensitization.